Hubungan Dukungan Sosial Keluarga Dengan Stress Akademik Pada Mahasiswa Sarjana Keperawatan FPOK UPI - Andini; Suparto, Tirta Adikusuma; Dharmansyah, Dhika; Puspita, Asih Purwandari Wahyoe; Adam, Rafi Jachra (Yayasan Healing and Healthcare Education, 2025)
Stress is an unavoidable part of human life. Nursing students face a demanding learning process that includes academic activities, clinical practice, observation, report writing, coursework, and practicals. Family social support plays a crucial role in managing academic stress among nursing students. The purpose of this study is to examine the relationship between family social support and academic stress in nursing students. This research employs a descriptive quantitative method with a cross-sectional approach. The study involved 177 undergraduate nursing students from FPOK UPI. Data were collected using questionnaires that measred levels of family social support and academic stress. Spearman correlation tests were used to analyze the relationship between the two variables. The study found that 51.98% of students had very high family social support, and 50.85% of students experienced low levels of academic stress. The Spearman rank correlation test showed significant results (P<0.001), indicating a negative relationship between family social support and academic stress. This study demonstrates that family social support plays an important and positive role in reducing the level of academic stress among undergraduate nursing students at the Indonesian University of Education, Bandung.